MRI Atlas of the Human Deep Brain - Lemaire, Jean-Jacques; De Salles, Antonio; Coll, Guillaume; El Ouadih, Youssef; Chaix, Rémi; Coste, Jérôme; Durif, Franck; Makris, Nikos; Kikinis, Ron (Frontiers in Neurology, 2019)
no abstract